Evaluation of the tubular penetration of two different types of nanoparticle root canal sealers over apically separated files: a scanning electron microscopic study (in vitro study) - Alaa H. Nagdi; Nayera A. Mokhless; Mahmoud R. Aboelseoud (BMC Oral Health)
Abstract Background The separation of root canal instruments can significantly impact the quality of canal obturation and the long-term success of endodontic treatment. Combining the benefits of nanoparticles and ultrasonic activation aim to enhance tubular sealer penetration and achieve proper sealing to improve outcome in such complex cases. Aim of the study This study aimed to evaluate tubular penetration of two nanoparticles modified root canal sealers compared to conventional sealers using ultrasonic activation over an apically separated file analyzed by scanning electron microscopy (SEM). Materials and methods Forty extracted single canaled mandibular premolar teeth were decoronated and prepared using M-Pro (IMD, Shanghai, China) nickel titanium rotary files which were intentionally separated at apical third. Teeth were randomly divided into four equal groups based on the type of sealer used. Group I: Adseal (Rs) (Meta Biomed, Cheongju, Korea) resin-based sealer, group II: Adseal resin-based sealer modified with silver nanoparticles (Rs/Ag), group III: Ceraseal (BC) (Meta Biomed, Cheongju, Korea) bioceramic sealer and group IV: Ceraseal bioceramic sealer modified with bioactive glass nanoparticles (BC/BG). The tested sealers were applied in all root specimens using lentulo-spiral size #25 (Dentsply Maillefer, Ballaigues, Switzerland) except the BC group where the sealer was injected into the root using plastic delivery tips provided by the manufacturer. All sealers were ultrasonically activated then obturated using cold lateral compaction technique. All samples were sectioned longitudinally in a buccolingual direction and analyzed for tubular sealer penetration using SEM at the area of separated file. Results The maximum mean tubular sealer penetration depth, measured in microns, was evident in the BC sealer group (97.00 ± 14.78) followed by the Rs/Ag group (94.12 ± 15.89) with no significant difference between them (p = 1.00). However, a significant difference (p < 0.05) was found when comparing these groups to the Rs group (73.00 ± 7.53) and the BC/BG group (69.78 ± 15.19). No significant difference (p = 1.00) was observed between the Rs and BC/BG groups. Conclusions Under the parameters of this in vitro study, conventional bioceramic sealer and resin-based sealer modified with silver nanoparticles exhibit more tubular penetration depth over apically separated file compared to conventional resin-based sealer and bioceramic sealer modified with bioactive glass nanoparticles.